2022
DOI: 10.5812/compreped.119997
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorders in Children with Functional Constipation: A Case-Control Study

Abstract: Background: Functional constipation is a common disorder in children, and evidence suggests that psychiatric disorders may induce functional constipation in children. The present study aimed to evaluate and compared anxiety disorders in children with and without functional constipation. Methods: This case-control study was conducted on 200 children (100 cases with functional constipation and 100 children without functional constipation) aged 15 - 8 years. The participants’ age and gender were evaluated and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Another study on 996 adult patients with functional gastrointestinal disorders showed that patients with FI had specific personality characteristics (11). The studies on children usually evaluated the comorbidity of specific psychological disorders such as attention-deficit/hyperactivity disorder (ADHD) (12,13), autism spectrum disorder (ASD) (14,15), intellectual disability (ID) (16), and anxiety disorders (17) with FI. A few studies, especially in Iran, focused on emotional and behavioral problems in children with FI.…”
Section: Introductionmentioning
confidence: 99%
“…Another study on 996 adult patients with functional gastrointestinal disorders showed that patients with FI had specific personality characteristics (11). The studies on children usually evaluated the comorbidity of specific psychological disorders such as attention-deficit/hyperactivity disorder (ADHD) (12,13), autism spectrum disorder (ASD) (14,15), intellectual disability (ID) (16), and anxiety disorders (17) with FI. A few studies, especially in Iran, focused on emotional and behavioral problems in children with FI.…”
Section: Introductionmentioning
confidence: 99%
“…Patient characteristics: all eleven studies included 25,116 pediatric patients as a study sample, with an age range from 2 months to 17 years old [ 9 - 20 ]. Seven studies (63.6%) are mostly made up of males [ 10 - 13 , 15 , 16 , 18 ]. Rome criteria were utilized in most research (63.6%); three studies used Rome IV [ 9 , 10 , 13 ] and four used Rome III criteria to diagnose FC [ 11 , 14 , 17 , 19 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Rome criteria were utilized in most research (63.6%); three studies used Rome IV [ 9 , 10 , 13 ] and four used Rome III criteria to diagnose FC [ 11 , 14 , 17 , 19 ]. The remainder defined FC using based on a cluster of symptoms [ 12 , 15 , 16 , 18 ]. We found varied FC prevalence, ranging from 4.7-62.5%.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have noted the role of psychological factors in the development and persistence of FC. Depression, anxiety, and panic have been described to be related to constipation in several studies (14)(15)(16). Social anxiety is believed to be rooted in the child's low self-confidence, and also, chronic FC is associated with decreased selfconfidence in children due to its behavioral problems.…”
Section: Introductionmentioning
confidence: 99%